Evaluation Of Variation In Material Cost For Design Of Reinforced Concrete Buildings In Penang Island Considering Seismic Effect - Chan, Ying Wei (Universiti Sains Malaysia, 2021)
Malaysia is located in a seismically safe area except few places in Sabah. However, the construction industry in Malaysia will adopt Malaysian National Annex (NA) to Eurocode 8 due to instances that raised concerns about the integrity of existing buildings that were built without considering seismic loads. There is little information on the material cost increases if the earthquake-resistant design is implemented in Malaysia. This study aimed to determine the variation in material cost due to seismic loading, as well as the influence of building height and ground type on material cost. Building of 10 storey, 15 storey, 20 storey, 25 storey, and 30 storey were modelled for non-seismic design and seismic design in ground types A, D, and E. The material cost increment between non-seismic design and seismic design was determined. Besides that, the material cost increment of seismic design in different ground types were also determined. The reinforced concrete building was designed based on EC2 and designed according to EC 8 with peak ground acceleration reflecting the seismic hazard in Penang. The greater amount of reinforcement bar in EC 8 compared with EC 2 design leads to an increase in the material cost. However, compared with EC8, the provision of reinforcement bar according to EC2 is higher when the storey height is at 30 storey. The percentage of cost increment is found to be 11.45%, 20.05%, 10.02%, 5.08% and -10.22% for 10 storey, 15 storey, 20 storey, 25 storey and 30 storey buildings, respectively for ground type D. Besides that, the amount of reinforcement bar according to EC8 under ground type D compared to ground type A and E leads to increase in the material cost. Compared with soil type D, the material cost for ground type A decreases 5.24%, 2.06%, 4.84%, 9.10%, and 6.64% for 10 storey, 15 storey, 20 storey, 25 storey, and 30 storey buildings, respectively. Compared with soil type D, the material cost for soil type E decreases 2.61%, 1.71%, 2.25%, 0.08%, and 8.03% for 10 storey, 15 storey, 20 storey, 25 storey, and 30 storey buildings, respectively.